Market Dominance and Abuse of Dominant Position by Big Tech Companies: Challenges in Enforcing National Competition Law: Case Study: Grab and Gojek in Indonesia - Asmah Asmah; Indrahayu Umar Gazali (Journal of Progressive Law and Legal Studies, 2026)
This research analyzes the phenomenon of market dominance and potential abuse of dominant position by big tech companies, specifically Grab and Gojek (GoTo) in Indonesia's online transportation industry. These two digital platforms control more than 90% of the national ride-hailing market share, creating an oligopolistic market structure that potentially violates healthy business competition principles. This study employs a normative juridical method with a case study approach, analyzing decisions from the Business Competition Supervisory Commission (KPPU), competition law regulations, and recent academic literature from the 2024-2025 period. The research findings indicate that the market dominance held by Grab and Gojek creates entry barriers for new competitors through network effects, consumer data accumulation, and digital ecosystem control. The merger discourse between both companies in 2025 exacerbates concerns about monopolistic practices and declining welfare for consumers and driver partners. Challenges in enforcing competition law include the limitations of Law No. 5/1999, which has not accommodated digital market characteristics such as two-sided markets, algorithmic discrimination, and data-driven anti-competitive behavior. KPPU faces constraints in institutional capacity, difficulties in proving anti-competitive practices in the digital era, and cross-jurisdictional complexity. This research recommends modernizing competition law through revision of Law No. 5/1999, strengthening KPPU's capacity in digital forensics and algorithm analysis, and adopting ex-ante regulatory approaches to prevent excessive market concentration.